2018
DOI: 10.3892/mmr.2018.8541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin on the expression of AMPK and STAT3 in the spinal dorsal horn of rats with neuropathic pain

Abstract: Neuropathic pain (NP) is a frustrating and burdensome problem. Current treatments for NP have unendurable side effects and/or questionable efficacy, and once these therapies are stopped, the symptoms often return. Thus, novel drugs are needed to enhance the effectiveness of treatments for NP. One novel target for pain treatments is adenosine monophosphate-activated protein kinase (AMPK), which regulates a variety of cellular processes, including protein translation, which is considered to be affected in NP. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 48 publications
(67 reference statements)
3
29
1
Order By: Relevance
“…Furthermore, triclosan inhibited autophagy after si-AMPK transfection, which indicated that AMPK may be involved in triclosan-induced autophagy. Some studies have showed that AMPK activation suppresses the STAT3 signaling pathway (26,53,54); however, genetic or pharmacological inhibition of STAT3 significantly increases the ADP/ATP ratio and activates AMPK signaling (55,56). Therefore, there is a dual directional regulation mechanism between AMPK and STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, triclosan inhibited autophagy after si-AMPK transfection, which indicated that AMPK may be involved in triclosan-induced autophagy. Some studies have showed that AMPK activation suppresses the STAT3 signaling pathway (26,53,54); however, genetic or pharmacological inhibition of STAT3 significantly increases the ADP/ATP ratio and activates AMPK signaling (55,56). Therefore, there is a dual directional regulation mechanism between AMPK and STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Among these protein kinase and transcription factors, the role of AMPK in spinal cord glial activation has been received attention in recent years. In CCI rats, phosphorylated-AMPK was expressed at lower levels in the dorsal spinal cord [64]. Moreover, activation of AMPK can effectively inhibit the activation of spinal microglia and astrocytes, which result in pain relief [64].…”
Section: Discussionmentioning
confidence: 99%
“…In CCI rats, phosphorylated-AMPK was expressed at lower levels in the dorsal spinal cord [64]. Moreover, activation of AMPK can effectively inhibit the activation of spinal microglia and astrocytes, which result in pain relief [64]. Lidocaine suppressed morphine-induced activation of spinal cord microglia and downregulated inflammatory cytokines production by activating AMPK [65].…”
Section: Discussionmentioning
confidence: 99%
“…Several signal molecules such as JNK, AMPKα1, and mTOR proteins are known to play important roles in the regulation of pain or antinociception [32][33][34]. However, the relationship of the expression of JNK, AMPKα1 and mTOR proteins and acute stress-induced antinociception in the spinal cord has not been reported.…”
Section: Discussionmentioning
confidence: 99%